The professionalization of the counsellor role - a comparative study of Finland and Norway - Ingrid Bårdsdatter Bakke; Samira Harjula (Taylor & Francis Group, 2024)
ABSTRACTCareer guidance counsellors' competence requirements in Norwegian schools have been the subject of decades-long discussion. Practitioners, experts, and stakeholders have called for precise requirements and professionalized status for counsellors, but with little results. In the Finnish context, however, career guidance is more professionalized, and the counsellor competence requirements are defined by law. Why have the two systems developed differently? In this research, we used 'historical institutionalism' as our lens and compared the two developmental histories of the counsellor role and the reasoning behind these differentiating systems. By utilizing Toulmin's model of argumentation, we analysed rationales in policy documents from ministries to expert groups to reveal how the policy rationales have formed the different statuses of the career counsellor profession in the 1950s, 1960s and 1990s. Norway and Finland saw the counsellor role similarly, but eventually, decisions on qualifications and competency were made from different perspectives.